XDR Surveillance in a Tertiary Care Hospital: A Periodic Observational Study - John, Jose; Chacko, Juby O.; Babu, Johnson V. (Journal of Pharmacy Practice and Community Medicine)
Background: The study focused on patients with XDR organisms and the risk factors to analyse the increase in trend of XDR colonised/infected patients from the community and hospital setting. Methodology: The study employed a periodic observational study conducted in a tertiary care hospital. The periodic selection of duration was based on the changes in antimicrobial resistance pattern identified previously in the hospital. The periods chosen was November-December 2018, May-June 2019, November- December 2019, May-June 2020 and November- December 2020. The study did not involve any sampling or experiment during the data procurement process even if it was a prospective study. The whole required details obtained from the patient medical record and microbiology laboratory. Results: The percentage of XDR isolate obtained were 5-6% from the total culture specimen. Klebsiella was the most identified organism in our study (70%). Initially colonisation was highest, when moving forward number of infected patients were rose. Major risk factors identified were prolonged antibiotic exposure (>50%), previous hospitalisation (>40%), catheter (70%), age (mean age- 58.2 years). The average hospitalisation duration was increased 3 times when compared normal hospitalisation. Conclusion: Although a few prospective studies have examined the relationship between the details of antibiotic exposure and resistance development, differentiating particular factors related to prior antimicrobial exposure and the development of resistance has been challenging.
Keywords: XDR; Resistance; Antibiotics; Infection; Colonisation.